BCG-trained macrophages couple LDLR upregulation to type I IFN responses and antiviral immunity - Yangdian Lai; Xiaoxu Yang; Dong Wei; Xin Wang; Ruiming Sun; Yunfei Li; Ping Ji; Yujie Bao; Tiancheng Chu; Chenxing Zhang; Qiming Liang; Jie Xu; et al. (Cell Reports)
Summary: Trained immunity refers to memory-like responses of innate immune cells when they re-encounter pathogenic stimuli. Bacillus Calmette-Guérin (BCG) vaccination implies enhanced antiviral immunity, whereas the underlying mechanisms remain unclear. Herein, we have uncovered elevated expression of low-density lipoprotein receptor (LDLR) on BCG-trained macrophages with robust type I interferon (IFNI) production and antiviral effects both in vivo and in vitro. Consequently, cholesterol is accumulated in BCG-trained macrophages, leading to the augmentation of NFE2L1 expression and the formation of NFE2L1/IRAK1/TRIM25 complex where TRIM25 mediates IRAK1 K63 polyubiquitination to exaggerate IFNI responses in an RIG-I-dependent manner. We have also observed LDLR+ macrophages displaying heightened IFNI responses in BCG-treated human macrophages. To antagonize LDLR degradation by PCSK9 inhibitors increases IFNI responses in the macrophages and accelerated viral clearance. Our study thus couples LDLR upregulation to antiviral activity in BCG-trained macrophages, making commercial PCSK9 inhibitors potential antiviral indications in clinic.